Analisis Alih Kode dan Campur Kode pada Gelar Wicara Mata Najwa dan Implikasinya terhadap Pembelajaran Bahasa Indonesia di SMA - Saraswati Saraswati; Purlilaiceu Purlilaiceu; Nurul Afni Hanifah (Universitas Mathla'ul Anwar Banten, 2022)
This study describes most of the speech forms that contain symptoms of code switching and code mixing as well as a description of the intentions or factors causing the symptoms of code switching and code mixing. The data source for this research is a video showing the speech title